ASEAN's Regional Integration Challenge: The ASEAN Process - Benny Teh Cheng Guan (The Copenhagen Journal of Asian Studies, 2004)
ASEAN's development, though gradual and slow, has consistently demonstrated an uphill shift from a focus on regional peace and stability to closer economic integration. Amid economic difficulties, ASEAN took on the task of setting goals for the region as clearly laid out by Vision 2020. The vision for the future goes beyond the two-page Bangkok Declaration set in 1967. The ultimate goal is to achieve an integrated ASEAN community with a common regional identity. Considering the downturns and problems that are affecting the organization, scholars have argued that successful integration is highly unlikely for ASEAN. The route is laden with obstacles that urgently need to be cleared. Based on this understanding, the paper first reviews the analysis of the determinants of the success and failure of regional integration. It then attempts to show that there lies a deeper root cause of concern, one that has been fundamentally imbedded and has come to dictate the working traditions of ASEAN. Proper reconfiguration and supplementation of the ASEAN process is a key necessity to reviving ASEAN's dynamism and competitiveness and as such should not be sidelined any longer.